ABDULLAH ALMIGHTY'S CONTRIBUTION TO OUR LITERARY LANGUAGE, THE BEAUTY OF SPEECH (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article discusses the contribution of Abdullah Almighty, the founder of Uzbek novels and considered proud of our nation, to our literary language, the development of our speech, and the development of the Uzbek language.